Abstract 076: 2023 Fusarium Meningitis Outbreak: Neuroendovascular Outcomes and Observations of the Angioinvasive Disease from South Texas - Kaiser O Sadiq; Sohum K Desai; Yazan D Abualnadi; Zorain M Khalil; Samantha Miller; Vijay Ravindra; Wondwossen G Tekle; Alexandros E Georgiadis; Ameer E Hassan (Stroke: Vascular and Interventional Neurology)
Introduction The Centers for Disease Control and Prevention (CDC) issued a health advisory in response to an outbreak of Fusarium meningitis from exposure to spinal anesthesia for cosmetic surgery performed in Mexico between Jan 1 to May 13, 2023. This paper outlines the neuroendovascular and neurosurgical observations and management of this outbreak at our Comprehensive Stroke Center with a focus on angio‐invasive disease. Methods A retrospective chart review was performed for fungal meningitis patients that presented between April and July 2023. Results There were a total of 12 patients who were found to have fungal meningitis, 11 of whom were included in the final analysis with angio‐invasive Fusarium solani. The mean age was 31.7 ± 7.15. 92% of patients were female. CT and MRI were initially normal in two‐thirds of patients. No cases demonstrated positive growth on fungal cultures. Only (1→3)‐β‐D‐Glucan assays were positive in all patients who were tested. After several patients in this series developed subarachnoid hemorrhage from a ruptured mycotic aneurysm, we proceeded to institute weekly cerebral angiography protocol. This detected moderate to severe vasospasm in 75%, and aneurysms in 58%, with the most common site being the basilar artery. The aneurysms were seen exclusively in the posterior circulation. The average size of aneurysms when first detected was 5.0 ± 3.8 mm. Patients with brain aneurysms were treated with flow diversion in 57% of cases, primary coiling was performed in 14%, and the remaining expired prior to treatment. 14% in our series actually developed another episode of subarachnoid hemorrhage after treatment from a new angiographically confirmed aneurysm. All patients who presented with subarachnoid hemorrhage from mycotic aneurysms have passed or withdrawn care. With regard to vasospasm treatment, 80% had treatment with intra‐arterial verapamil and 40% underwent mechanical angioplasty. We did not perform balloon angioplasty in any case due to concern for rupture of the weakened compromised vessel walls. Finally with regard to cerebrospinal fluid (CSF) diversion; 67% underwent ventriculostomy, and a minority were converted to ventriculoperitoneal shunts. All but one patient received dual antifungal therapy with Amphotericin B and Voriconazole, and 42% were started on every other day intrathecal Amphotericin B. Conclusion We have found that in patients with fusarium meningitis that weekly angiographic surveillance for aneurysms and vasospasm should be performed. Conventional angiography is preferred to computed tomography angiography due to the smaller size of aneurysms. Aneurysms should be primarily coiled prior before flow diversion is attempted, and vasospastic vessels may be mechanically dilated in the setting of vessel wall necrosis.